2010
DOI: 10.1007/s12250-010-3152-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of rice gall dwarf virus outer coat protein gene (S8) in insect cells

Abstract: To obtain the P8 protein of Rice gall dwarf virus (RGDV) with biological activity, its outer coat protein gene S8 was expressed in Spodoptera frugiperda (Sf9) insect cells using the baculovirus expression system. The S8 gene was subcloned into the pFastBac™1 vector, to produce the recombinant baculovirus transfer vector pFB-S8. After transformation, pFB-S8 was introduced into the competent cells (E. coli DH10Bac) containing a shuttle vector, Bacmid, generating the recombinant bacmid rbpFB-S8. After being infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In recent years, RGDV has spread to Guangdong, Hainan and Guangxi Provinces of southern China 26 . RGDV is mainly transmitted in a persistent-propagative manner by the leafhopper vector with high efficiency, and the virus has evolved to adapt to the vector 26 27 28 . Both leafhopper R. dorsalis and its cultured cells support the multiplication of RGDV to a high titer and in both, a persistent and nonlethal infection develops 26 29 30 .…”
mentioning
confidence: 99%
“…In recent years, RGDV has spread to Guangdong, Hainan and Guangxi Provinces of southern China 26 . RGDV is mainly transmitted in a persistent-propagative manner by the leafhopper vector with high efficiency, and the virus has evolved to adapt to the vector 26 27 28 . Both leafhopper R. dorsalis and its cultured cells support the multiplication of RGDV to a high titer and in both, a persistent and nonlethal infection develops 26 29 30 .…”
mentioning
confidence: 99%
“…The immunofluorescence analysis showed that P8 protein of RGDV formed punctuate structures in the cytoplasm of Sf9 cells. This system was used to overcome the insolubility of the expression products using prokaryotic expression system (Fan et al 2010). Scanning electron microscope of infected insect cells using the recombinant vAc-polh-TYLCV-CP showed geminated, icosahedral virus-like particles (VLP) typical to Begomovirus particles (20 9 30 nm).…”
Section: Discussionmentioning
confidence: 99%